Hermanna Brocha analiza faszyzmu - Lichański, Jakub Z.; Ganczar, Maciej (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2018)
Like many other German-speaking writers, Hermann Broch was forced to emigrate from Nazi Germany at the end of the 1930s. It was partly due to the criticism of the fascist movement that he had presented in the then-titled Bergroman [Mountain Novel], which took its final shape as Der Versucher [The Seducer] and was published posthumously under the title The Spell [Die Verzauberung]. Another novel depicting the development of fascism is Broch’s Die Schuldlosen: Ein Roman in elf Erzählungen [The Guiltless Ones. A Novel in Eleven Stories]. Broch also wrote Adolf Hitler’s Farewell Address, an essay that can be read as a sort of completion to the abovementioned books since it providesan even more directinsight into the Nazi mind, portraying it from within. In his works, Hermann Broch describes spiritual as well as specifically social roots of fascism: any autocratic movement characterized by the rejection of Platonic idealism and thus, inevitably, of the Christian tradition itself.